Human Resource Management Strategy in Community-Based Tourism Business in Lake Toba Area - Yudhistira, Prima; Daryana, Aditiya Pratama (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
This study aims to explore human resource management (HRM) strategies applied in community-based tourism businesses in the Lake Toba area. Using a qualitative descriptive-exploratory approach, data were collected through in-depth interviews, participant observation, and document analysis involving tourism actors in three tourism villages: Tipang, Lumban Bulbul, and Sigapiton. The results showed that HRM strategies are still informal and highly dependent on local institutional capacity and external support. Effective practices are characterized by the existence of structured community organizations, ongoing training, and multi-party collaboration. This study concludes that community-oriented HRM that is adjusted to local values ​​plays an important role in improving service quality, institutional sustainability, and community economic empowerment.